Global Student Teacher Transformation Experiences: Living the Faith through the Shared Christian Praxis Learning Process - Quezada, Reyes L. (Catholic Education: A Journal of Inquiry and Practice, 2011)
This study examined the reflections of six university student teachers from a Catholic university who participated in an international student teaching setting and sought to evaluate how they developed a global teaching ideology while student teaching abroad. Thomas Groome’s Shared Christian Praxis Learning Process was used as a lens to examine the reflections of the student teachers. Using qualitative measures, the data analysis revealed four themes: (1) development of world citizens, (2) developing as a globally competent professional educator, (3) new knowledge of cultural and comparative educational systems, and (4) self-monitoring for improvement of efficacy and instructional practice.